2015
DOI: 10.1093/annonc/mdu551
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant treatment with docetaxel plus lapatinib, trastuzumab, or both followed by an anthracycline-based chemotherapy in HER2-positive breast cancer: results of the randomised phase II EORTC 10054 study

Abstract: NCT00450892.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 24 publications
2
83
0
1
Order By: Relevance
“…In addition to NeoALTTO 28 , other neoadjuvant studies have investigated the addition of lapatinib to trastuzumab for the treatment of patients with HER2-positive breast cancer 42, 55, 65 . The Cancer and Leukemia Group B 40601 trial (CALGB 40601) 42 quantified the pCR rates of patients who received weekly paclitaxel and either trastuzumab plus lapatinib or trastuzumab alone; the pCR rate was modestly higher with combined dual-agent HER2 blockade, but this difference did not reach statistical significance: 51% (95% CI 42–60) versus 40% (95% CI 32–49), P = 0.11).…”
Section: Pcr As a Surrogate For Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to NeoALTTO 28 , other neoadjuvant studies have investigated the addition of lapatinib to trastuzumab for the treatment of patients with HER2-positive breast cancer 42, 55, 65 . The Cancer and Leukemia Group B 40601 trial (CALGB 40601) 42 quantified the pCR rates of patients who received weekly paclitaxel and either trastuzumab plus lapatinib or trastuzumab alone; the pCR rate was modestly higher with combined dual-agent HER2 blockade, but this difference did not reach statistical significance: 51% (95% CI 42–60) versus 40% (95% CI 32–49), P = 0.11).…”
Section: Pcr As a Surrogate For Survivalmentioning
confidence: 99%
“…The authors also analysed the results according to gene-expression-based intrinsic molecular subtypes, and gene sequence and copy-number abnormalities in primary tumours and residual disease; these studies revealed that pCR rates were higher among the patients with a specific molecular disease subtype defined as ‘HER2-enriched’ 42, 66 . In addition, the National Surgical Adjuvant Breast and Bowel Project (NSABP) B-41 trial 55 and European Organisation for Research and Treatment of Cancer (EORTC) 10054 trial 65 randomly assigned patients to receive neoadjuvant chemotherapy with either trastuzumab, lapatinib, or the combination of both anti-HER2 agents. The dual-agent HER2-targeted therapy was associated with numerically higher, but not statistically significant, pCR rates than single-agent HER2-directed therapy in both trials 55,65 .…”
Section: Pcr As a Surrogate For Survivalmentioning
confidence: 99%
“…Some studies are phase II clinical trials for instance TBCRC 006, EORTC 10054, CHER-LOB [67][68][69], the others are phase III clinical trials such as the NOAH trial, NeoALTTO, CALGB 40601, NSABP protocol B-41, the Adjuvant Lapatinib and/or Trastuzumab Treatment Optimization Trial [70][71][72][73]. Such studies have the potential to produce parameters that will inform future modelling exercises.…”
Section: Modellingmentioning
confidence: 99%
“…[11] The combination of lapatinib and trastuzumab sequential with chemotherapy has resulted in statistically significant pCR rates. [12,13] In addition, secondary endpoints of event free survival and 3 years overall survival for patient experiencing pCR were superior to the outcomes of patients who did not. [14] The promise of this treatment strategy has faded with the presentation of the ALTTO, which failed to show any survival benefit for the combination in the adjuvant setting.…”
Section: Introductionmentioning
confidence: 99%